EFFECT OF ORGANIC MANURES AND BIOFERTILIZERS ON PLANT GROWTH, AND YIELD TRAITS OF TOMATO (SOLANUM LYCOPERSICUM MILL.) VAR. PUSA RUBY (International Journal of Food and Nutritional Sciences, 2023)
Present investigation entitled “Effect of organic manures and biofertilizers on plant growth, yield and quality traits of Tomato (Solanum lycopersicum Mill.)” var. Pusa Ruby” was conducted during the Rabi season of 2024 - 25 at Agriculture Research Farm, Rama university, Mandhana, Kanpur. The experiment was laid out in Randomized Block Design (RBD) with three replications and nine treatments viz. T1= Control, T2=FYM Poultrymanure @ 8t/ha,T3=Vermicompost @ 8 t/ha, T4= Neemmanure@ 5 t/ha T5 =BiovitaGranules@20kg/ha,T6=Biofertilizers(Azotobacter+PSB+KSB)each@5kg/ha,T7 =FYM Poultry manure @ 8 t/ha + Biofertilizers (Azotobacter) @ 5 kg/ha, T8=Vermicompost @ 8 t/ha + Biofertilizers (PSB) @ 5 kg/ha and T9=Vermicompost @ 8 t/ha + Biofertilizers (PSB) @ 5 kg/ha. The result of the study revealed that the maximum plant height (156.40cm), Number of leaves (98.50), leaf area index (0.960cm), canopy spread (0.243), Days to first flower (40.4), Number of branches per plant (18.49), Number of flowers / plant (32.29), Number of fruit/ plant (20.06), fruit diameter (7.02cm), fruit weight (68.80gm), Basis on these results treatment T6can be suggested to the local farmer of Kanpur regions to obtain higher yield and net return in tomato.